Method for processing battery

The method addresses the environmental burden of high-temperature battery processing by heating and pulverizing at lower temperatures to peel the active material layer efficiently, achieving high peeling rates with reduced thermal energy consumption and emissions.

JP2024174186AInactive Publication Date: 2024-12-13TOYOTA JIDOSHA KK
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2024173182
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2024-10-02
Publication Date
2024-12-13
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing battery processing methods consume large amounts of thermal energy and emit significant carbon dioxide due to high-temperature heating to decompose the binder in the active material layer, leading to a substantial environmental burden.

Method used

A battery processing method that heats the pulverized material at a temperature lower than the decomposition peak of the resin component to soften it, followed by pulverization, thereby peeling the active material layer from the electrode substrate while reducing thermal energy consumption and carbon dioxide emissions.

Benefits of technology

The method efficiently separates the active material layer from the electrode substrate with minimal environmental impact by softening the resin component at a lower temperature, achieving a peeling rate of 80% or more with particle sizes suitable for easy separation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2024174186000001_ABST
    Figure 2024174186000001_ABST
Patent Text Reader

Abstract

To provide a method for processing a battery which can separate an active material layer from an electrode substrate while reducing an environmental load.SOLUTION: The method for processing a battery includes the steps of: discharging a secondary battery and setting a voltage at a value which is a predetermined level at a maximum; crushing the secondary battery and obtaining a crushed material including an active material, a binder, an electrolyte, and a metal foil; heating the crushed material at a first temperature under a reduced-pressure and evaporating the electrolyte; and further crushing the crushed material and separating the active material from the metal foil.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a battery processing method for peeling off an active material layer from an electrode substrate. [Background technology]

[0002] Secondary batteries, in which an electrolyte and a battery element are housed inside a housing, are widely used as power sources for electronic devices such as video cameras, notebook computers, and mobile phones, as well as electric vehicles, hybrid vehicles, etc. For this reason, from the viewpoint of effective utilization of resources, it is considered important to recover recycled materials such as valuable metals from used secondary batteries or secondary batteries discarded before use.

[0003] As such, JP 2012-195073 A (Patent Document 1) discloses a battery processing method for recovering recycled materials such as valuable metals, in which a secondary battery is pulverized to remove the separator, the pulverized material including the electrode substrate and active material layer is heated in the range of 400°C to 550°C, and the heated pulverized material is further pulverized. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2012-195073 A Summary of the Invention [Problem to be solved by the invention]

[0005] However, in the battery treatment method disclosed in Patent Document 1, the active material layer is heated to 400°C to 550°C to decompose the binder contained therein, consuming a large amount of thermal energy. In addition, a large amount of binder is decomposed, and carbon dioxide is likely to be emitted. This results in a large burden on the environment.

[0006] The present disclosure has been made in consideration of the above-mentioned problems, and an object of the present disclosure is to provide a battery treatment method capable of peeling off an active material layer from an electrode substrate while reducing the environmental burden. [Means for solving the problem]

[0007] The battery treatment method of the present disclosure includes the steps of preparing a pulverized material including an electrode substrate and an active material layer including a resin component and provided on the electrode substrate, heating the pulverized material at a temperature equal to or higher than a decomposition start temperature of the resin component and lower than a peak decomposition temperature of the resin component, and pulverizing the pulverized material. In the heating step, the resin component is softened, and in the pulverizing step, the pulverized material in a state in which the resin component is softened is pulverized to peel off the active material layer from the electrode substrate.

[0008] In the case of the above-mentioned configuration, the pulverized material is heated at a temperature equal to or higher than the decomposition start temperature of the resin component and lower than the peak decomposition temperature of the resin component, so that the resin component can be softened at a low temperature while suppressing the consumption of thermal energy. In addition, since the decomposition of the resin component can be suppressed, the amount of carbon dioxide emitted can also be reduced. Furthermore, by pulverizing the pulverized material in which the resin component is softened, the active material layer can be peeled off from the electrode substrate. In this way, the active material layer can be peeled off from the electrode substrate while reducing the environmental load.

[0009] In the battery treatment method of the present disclosure, when the fragments of the electrode substrate from which the active material layer has been peeled off are spread out in a plane, the particle size of the fragments is 400 mm 2 More than 1000mm 2 or less, and the peeling rate of the active material layer from the electrode substrate may be 80% or more.

[0010] With the above-mentioned configuration, even if the fragments of the electrode substrate from which the active material layer has been peeled are relatively large, the active material layer can be efficiently peeled off from the electrode substrate.

[0011] In the battery treatment method of the present disclosure, the heating step and the pulverizing step may be carried out simultaneously.

[0012] When the above configuration is used, heating and crushing are performed simultaneously, so there is no need to heat the crushed material and then transport the heated crushed material to the crushing process, thereby simplifying the processing process.

[0013] In the battery treatment method of the present disclosure, the heating step and the pulverizing step may be performed repeatedly.

[0014] With the above-mentioned configuration, the resin component contained in the active material layer adhering to the crushed pieces of the electrode substrate can be further softened, and the active material layer can be further peeled off from the pieces of the electrode substrate.

[0015] In the battery treatment method of the present disclosure, it is preferable that in the preparing step, the pulverized material includes a separator, and it is preferable that in the pulverizing step, the separator, the electrode substrate, and the active material layer are separated.

[0016] According to the above-mentioned configuration, since the pulverized material can be heated at a low temperature, it is possible to prevent the separator from being welded to the active material layer, and even if the pulverized material contains a separator, it is possible to separate the active material layer from the electrode plate. Therefore, a step of removing the separator in advance is not necessary, and the processing steps can be simplified. Effect of the Invention

[0017] According to the present disclosure, it is possible to provide a battery processing method capable of separating an active material layer from an electrode substrate while reducing the environmental load. [Brief description of the drawings]

[0018] [Figure 1] FIG. 2 is a flow chart showing steps of a battery treatment method according to the first embodiment. [Diagram 2]FIG. 4 is a schematic diagram showing a step of heating the pulverized material according to the first embodiment. [Diagram 3] FIG. 3 is a schematic diagram showing a pulverization step according to the first embodiment. [Figure 4] 13 is a schematic diagram showing a case where a step of heating the pulverized material and a step of pulverizing the pulverized material are carried out simultaneously in a battery treatment method according to a modified example. FIG. [Diagram 5] FIG. 11 is a flow chart showing steps of a battery treatment method according to a second embodiment. [Figure 6] FIG. 1 is a diagram showing the conditions and results of an experiment conducted using a battery treatment method according to an embodiment and a battery treatment method in a comparative example. [Figure 7] FIG. 7 is a diagram in which the relationship between particle size and peeling rate is plotted for each of Comparative Examples 1-8 and Examples 1-2 shown in FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0019] Hereinafter, embodiments of the present disclosure will be described in detail with reference to the drawings. In the embodiments described below, the same or common parts are denoted by the same reference characters in the drawings, and the description thereof will not be repeated.

[0020] (Embodiment 1) Fig. 1 is a flow diagram showing steps of a battery treatment method according to embodiment 1. The battery treatment method according to embodiment 1 will be described with reference to Fig. 1.

[0021] The battery treatment method according to the first embodiment is a method used for recovering an active material layer that contains valuable metals and the like.

[0022] The battery treatment method is directed to a secondary battery such as a lithium ion battery, etc. The secondary battery includes a battery element, an electrolyte, and an exterior case that contains the battery element and the electrolyte.

[0023] The battery element is constructed by stacking a positive electrode and a negative electrode with a separator interposed between them.

[0024] The positive electrode includes a sheet-like member as an electrode substrate and a positive electrode active material layer. The sheet-like member is made of a metal foil such as aluminum foil. The positive electrode active material layer may be formed on both sides of the sheet-like member. The positive electrode active material layer includes a positive electrode active material and a binder as a resin component.

[0025] The positive electrode active material is typically a lithium (Li)-containing metal oxide. Specifically, the positive electrode active material is, for example, a lithium cobalt oxide-based material, a lithium manganese oxide-based material, or a lithium nickel cobalt manganese oxide-based material.

[0026] The binder may be, for example, carboxymethyl cellulose (CMC), styrene butadiene rubber (SBR), polyacrylic acid (PAA), and the like.

[0027] The negative electrode includes a sheet-shaped member and a negative electrode active material layer. The sheet-shaped member is made of a metal foil such as a copper foil. The negative electrode active material layer may be formed on both sides of the sheet-shaped member.

[0028] The negative electrode active material layer includes a negative electrode active material and a binder. The negative electrode active material may be, for example, a carbon-based negative electrode active material such as graphite, graphitizable carbon, or non-graphitizable carbon, or may be an alloy-based negative electrode active material containing silicon (Si), tin (Sn), or the like.

[0029] The binder may be, as described above, for example, carboxymethyl cellulose (CMC), styrene butadiene rubber (SBR), polyacrylic acid (PAA), or the like.

[0030] The separator is an electrically insulating porous film. The separator is made of, for example, a resin such as polyethylene (PE) and polypropylene (PP). The separator may be made of a PE porous film alone, or may be made of a PE porous film and a PP porous film in combination. For example, the separator may be made by laminating a PP porous film, a PE porous film, and a PP porous film in this order. For example, the separator may be made by laminating a PE porous film and a PP porous film.

[0031] The electrolyte is, for example, a solution of a lithium salt such as lithium hexafluorophosphate (LiPF6) dissolved in a mixed solvent such as ethylene carbonate (EC)-dimethyl carbonate (DMC), but may have a different composition. The exterior case is made of a metal such as aluminum.

[0032] As shown in FIG. 1, when carrying out the battery treatment method according to the first embodiment, first, in step (S10), a pulverized material is prepared.

[0033] To carry out step (S10), first, in step (S11), the secondary battery is deactivated. Specifically, the secondary battery is discharged or the like to reduce the voltage of the secondary battery to a predetermined value or less so that the secondary battery no longer functions as a battery.

[0034] Next, in step (S12), the secondary batteries are crushed. For example, the secondary batteries may be crushed using a single-axis shear crusher or a double-axis shear crusher, or may be crushed using a hammer mill or other crushing machine.

[0035] Subsequently, in step (S13), the electrolytic solution is recovered. Specifically, the pulverized material obtained in step (S12) is heated under reduced pressure to distill the electrolytic solution. At this time, solvents having a relatively low boiling point of about 90°C to 110°C, such as DMC and EMC (ethyl methyl carbonate), contained in the electrolytic solution, are easily recovered, while solvents having a relatively high boiling point of about 240°C, such as EC, contained in the electrolytic solution, may remain without being recovered.

[0036] Through the above-mentioned steps, a pulverized material 1 (see FIG. 2) is prepared, which includes the sheet member and an active material layer that includes a binder and is provided on the sheet member. More specifically, a pulverized material 1 is prepared that includes a positive electrode active material and a positive electrode sheet member. The pulverized material 1 may include a separator. In the first embodiment, the pulverized material 1 prepared is a primary pulverized material obtained by pulverizing a secondary battery.

[0037] Fig. 2 is a schematic diagram showing a step of heating the pulverized material according to embodiment 1. As shown in Fig. 1 and Fig. 2, next, in step (S20), the pulverized material 1 is heated at a temperature equal to or higher than the decomposition start temperature of the binder and lower than the decomposition peak temperature of the binder. The decomposition start temperature of the binder is, for example, about 120°C, and the decomposition peak temperature of the binder is, for example, about 400°C.

[0038] In step (S20), in order to soften the binder with lower thermal energy, the temperature range to which the pulverized material is heated is preferably about 120°C to 180°C. If the pulverized material contains a separator, the temperature is preferably about 120°C to 160°C, more preferably about 120°C to 140°C, in order to suppress melting of the separator. Furthermore, if the pulverized material 1 contains a separator, it is more preferable to heat the pulverized material 1 at a temperature equal to or higher than the decomposition start temperature of the binder and lower than the melting point of the separator.

[0039] When heating the pulverized material 1, for example, the pulverized material 1 is placed in a heating chamber 10 and heated by a heat source 20 such as a heater. Heating of the pulverized material 1 is not limited to heating by a heater, and any suitable heating method such as convection heating, far-infrared heating, steam heating, etc. may be used. The heating time is, for example, about 1 hour.

[0040] By heating the pulverized material 1 within the above-mentioned temperature range, the binder is softened, making it easier to separate the active material layer from the sheet-shaped member.

[0041] Fig. 3 is a schematic diagram showing the pulverizing step according to the first embodiment. As shown in Figs. 1 and 3, the heated pulverized material 1 is subsequently pulverized in step (S30). Specifically, for example, the heated pulverized material 1 is accommodated in a pulverizing chamber 30, and the pulverized material 1 is pulverized using a pulverizer 40. Note that the pulverizer 40 may be an appropriate pulverizer such as a hammer crusher. When a hammer crusher is used, the friction applied to the pulverized material 1 can be increased.

[0042] In step (S30), the pulverized material 1 is pulverized with the binder in a softened state, so that the active material layer can be peeled off from the sheet-like member by the impact applied to the pulverized material 1.

[0043] In the above, the case where step (S30) is performed after step (S20) is exemplified, but as shown in the modified example, step (S20) and step (S30) may be performed simultaneously. In this case, since heating and grinding of the pulverized material 1 are performed simultaneously, it is not necessary to transport the heated pulverized material 1 to the grinding step after heating the pulverized material 1, and therefore the processing steps can be simplified.

[0044] Fig. 4 is a schematic diagram of a battery treatment method according to a modified example, in which a step of heating the pulverized material and a step of pulverizing the pulverized material are performed simultaneously. When a step of heating the pulverized material and a step of pulverizing the pulverized material are performed simultaneously, as shown in Fig. 4, a heat source 20 such as a heater is installed in a pulverization chamber 30, and the pulverized material 1 is pulverized by a pulverizer 40 while heating the pulverized material 1. As described above, the heating of the pulverized material 1 is not limited to heating by a heater, and any suitable heating method such as convection heating, far-infrared heating, or steam heating can be used.

[0045] Next, in step (S35), it is confirmed whether the above steps (S20) and (S30) have been performed a predetermined number of times. The predetermined number of times may be once, or may be two or more times.

[0046] When the above steps (S20) and (S30) have been performed a predetermined number of times (step (S35): YES), step (S40) is carried out.

[0047] On the other hand, if the above steps (S20) and (S30) have not been performed the predetermined number of times (step (S35): NO), the steps (S20) and (S30) are repeatedly performed until the predetermined number of times is reached.

[0048] When steps (S20) and (S30) are repeatedly performed in this manner, the resin component contained in the active material layer adhering to the crushed electrode substrate fragments is further softened, and the fragments are crushed, whereby the active material layer can be further peeled off from the electrode substrate fragments.

[0049] Next, in step (S40), the pulverized material 1 is separated. Specifically, a sieve or the like is used to separate the sheet-like member and the active material layer. At this time, in addition to the sheet-like member and the active material layer, the separator and the members constituting the outer case are also separated. The pulverized material 1 separated in the first embodiment is a secondary pulverized material generated by pulverizing the primary pulverized material, and in step (S40), the secondary pulverized material is separated.

[0050] As described above, in the battery treatment method according to the first embodiment, the pulverized material is heated at a temperature equal to or higher than the decomposition start temperature of the resin component and lower than the peak decomposition temperature of the resin component, so that the resin component contained in the active material layer can be softened at a low temperature while suppressing the consumption of thermal energy. In addition, since the decomposition of the resin component can be suppressed, the amount of carbon dioxide emitted can also be reduced. Furthermore, by pulverizing the pulverized material in which the resin component is softened, the active material layer can be peeled off from the electrode substrate. In this way, the active material layer can be peeled off from the electrode substrate while reducing the environmental load.

[0051] In addition, when the fragments of the sheet-like member (positive electrode sheet-like member) from which the active material layer (more specifically, the positive electrode active material layer) has been peeled off are spread out in a plane, the particle size of the fragments is 400 mm 2 More than 1000mm 2 The peeling rate of the active material layer from the sheet-like member is preferably 80% or more.

[0052] The particle size of the fragments can be calculated as follows. First, in step (S40), fragments (particles) of the sheet-like members from which the active material layer has peeled off are sampled, and the fragments of the sheet-like members are spread out in a plane. Then, the size of the fragments of the sheet-like members spread out is calculated using image analysis software WinROOF (manufactured by Mitani Shoji Co., Ltd.).

[0053] Particle size (mm 2 ) can be obtained, for example, by calculating the sum of the values ​​obtained by dividing the area (projected area) of each particle by the total area (total projected area) of multiple particles. More specifically, it can be calculated by the following formula (1). TIFF2024174186000002.tif17147

[0054] The peeling rate can be calculated by calculating the total area of ​​the active material layer remaining on the pieces (particles) of the plurality of sheet-like members using the image analysis software, and then using the following formula (2).

[0055] Peeling rate (%) = (total area of ​​multiple (n) particles - total area of ​​active material layer remaining on multiple (n) particles) / total area of ​​multiple particles × 100 (Equation 2) (Embodiment 2) 5 is a flow diagram showing steps of the battery treatment method according to embodiment 2. The battery treatment method according to embodiment 2 will be described with reference to FIG.

[0056] 5, the battery treatment method according to the second embodiment differs from the battery treatment method according to the first embodiment in the step (S10A) of preparing a pulverized material, while the other steps are almost the same.

[0057] In carrying out the battery treatment method according to the second embodiment, first, in step (S10A), a pulverized material is prepared. In carrying out step (S10A), steps (S11) to (S13) are carried out in substantially the same manner as in the first embodiment.

[0058] Next, in step (S14), the pulverized secondary battery is further pulverized. Specifically, the primary pulverized material produced in step (S13) is pulverized. In step (S14), the primary pulverized material is pulverized using an appropriate pulverizer.

[0059] Subsequently, in step (S15), the secondary battery pulverized in step (S14) is separated. Specifically, the secondary pulverized material generated by pulverizing the primary pulverized material is separated. This prepares a pulverized material including a sheet member and an active material layer including a binder and provided on the sheet member. In this manner, the pulverized material prepared in the second embodiment is a sheet member provided with the active material layer separated from the secondary pulverized material. The sheet member is preferably a positive electrode sheet member, and the active material layer is preferably a positive electrode active material layer including a binder. The prepared pulverized material may include a separator.

[0060] Next, steps (S20) to (S40) are performed in a manner similar to that of embodiment 1. As described above, even when the battery treatment method according to embodiment 2 is performed, substantially the same effects as those of embodiment 1 can be obtained. Note that, as described above, in steps (S20) to (S40), a sheet member provided with an active material layer is used as the pulverized material, and therefore, by performing step (S40), the sheet member and the active material layer are separated.

[0061] (Verification experiment) Fig. 6 is a diagram showing the conditions and results of an experiment performed using the battery treatment method according to the embodiment and the battery treatment method in the comparative example. Fig. 7 is a diagram plotting the relationship between particle size and peeling rate in each of Comparative Examples 1-8 and Examples 1-2 shown in Fig. 6. The verification experiment will be described with reference to Figs. 6 and 7.

[0062] As shown in Fig. 6, in Comparative Example 1 to Comparative Example 6, compared to the steps of the battery treatment method according to the above-mentioned embodiment 1, the heating step (S20) was omitted, and the pulverized material prepared in the preparation step (S10) was pulverized in the pulverization step (S30) without heating. In Comparative Examples 1 to 6, the pulverization conditions were changed so that pieces (particles) with different particle sizes were obtained. After pulverization, the sheet-like member (positive electrode sheet-like member) and the active material layer (positive electrode active material) were separated using a sieve or the like, and the particle size of the fragments of the sheet-like member and the peeling rate of the active material layer were calculated using the above-mentioned calculation method.

[0063] In Comparative Examples 7 and 8, compared to the steps of the battery treatment method according to the above-mentioned embodiment 1, the temperature at which the pulverized material is heated in the heating step (S20) is 110°C, which is lower than the decomposition start temperature of the resin component (binder), and the pulverized material heated at 110°C is pulverized in the pulverizing step (S30). In Comparative Examples 7 and 8, the pulverization conditions were changed so that pieces (particles) with different particle sizes were obtained. After pulverization, the sheet-like member and the active material layer were separated using a sieve or the like, and the particle size of the fragments of the sheet-like member and the peeling rate of the active material layer were calculated using the above-mentioned calculation method.

[0064] In Examples 1 and 2, battery treatment was performed based on the steps of the battery treatment method according to the above-mentioned embodiment 1. In this case, the temperatures at which the pulverized material was heated in the heating step (S20) were 180° C. and 300° C. Both of these temperatures were equal to or higher than the decomposition start temperature of the resin component and lower than the peak decomposition temperature of the resin component.

[0065] The crushed material heated at 180° C. and 300° C. was crushed in a crushing step (S30). After crushing, the sheet-like member and the active material layer were separated using a sieve or the like, and the particle size of the fragments of the sheet-like member and the peeling rate of the active material layer were calculated using the calculation method described above.

[0066] As shown in Figs. 6 and 7, in Comparative Example 2, the particle size was about 149.3 mm 2 When the particle size was small, the peeling rate was about 87.4%. However, when the active material layer was crushed to a small particle size, the material constituting the exterior case or the copper constituting the negative electrode was also mixed into the active material layer, and the separation between the active material layer and these materials was deteriorated.

[0067] In the case of Comparative Examples 1 and 3-6 where the particle size was increased in order to prevent the inclusion of foreign matter in the active material layer, the active material layer had high adhesion due to the omission of heating, and the peeling rate tended to decrease as the particle size increased. 2 Above this, the peeling rate was lower than 50%.

[0068] As in Comparative Example 7, the particle size is approximately 140.7 mm 2 When the particle size was 1.0 mm, the peeling rate was about 81.8%. However, as the particle size became smaller, the active material layer was contaminated with the material constituting the exterior case or the copper constituting the negative electrode, and the separation between these and the active material layer became poor.

[0069] When the particle size was increased as in Comparative Example 8 in order to prevent foreign matter from being mixed into the active material layer, the peeling rate decreased compared to Comparative Example 8, and the peeling rate was approximately 59.0%.

[0070] In contrast, in Example 1, the particle size was approximately 404.6 mm 2 The peeling rate was 88.6%, which was higher than those of Comparative Examples 1 to 8. Similarly, in Example 2, the particle size was about 909.5 mm 2 The peeling rate was 95.2%, which was higher than those of Comparative Examples 1 to 8.

[0071] Furthermore, in Examples 1 and 2, since the particle size was relatively large, it was possible to prevent the material constituting the outer case or the copper constituting the negative electrode from being mixed into the active material layer.

[0072] As described above, it has been experimentally confirmed that by heating the pulverized material at a temperature equal to or higher than the decomposition starting temperature of the resin component and lower than the peak decomposition temperature of the resin component, thereby suppressing consumption of thermal energy, softening the resin component contained in the active material layer at a low temperature, and pulverizing the pulverized material, it is possible to peel off the active material layer from the sheet-like member while reducing the environmental burden.

[0073] The embodiments and modifications disclosed herein are illustrative and not restrictive in all respects. The scope of the present invention is defined by the claims, and includes all modifications within the meaning and scope of the claims. [Explanation of symbols]

[0074] 1 material to be crushed, 10 heating chamber, 20 heat source, 30 crushing chamber, 40 crusher.

Claims

1. discharging the secondary battery to reduce the voltage to a predetermined value or less; pulverizing the secondary battery to obtain a pulverized material containing an active material, a binder, an electrolyte, and a metal foil; heating the ground material at a first temperature under reduced pressure to evaporate the electrolyte; and further pulverizing the pulverized product to peel off the active material from the metal foil.

2. The battery treatment method according to claim 1 , further comprising the step of heating the pulverized material at a second temperature that is equal to or higher than a decomposition start temperature of the binder and equal to or higher than the first temperature.

3. The battery treatment method according to claim 2 , wherein the first temperature is equal to or higher than 90° C. and equal to or lower than 110° C.

4. The battery treatment method according to claim 3 , wherein the second temperature is equal to or lower than 120° C. and equal to or lower than 180° C.

Citation Information

Patent Citations

  • A method for separating and recovering valuable components of waste power lithium batteries

    CN109193064A

  • Method for producing recycled material

    JP2012195073A

  • Method for processing electrolyte containing fluorine

    JP2013229326A

  • Method for processing lithium ion battery

    JP2017036489A

  • Processing system and processing method of waste lithium-ion battery

    JP2020142228A